Spectral, Electron Microscopical and Chemical Characteristics of the Gem-Quality Silica-Rich Rhodonite - Hatipoglu, Murat (Asian Journal of Chemistry, 2011)
Large-sized massive masses of gem-quality silica-rich Anatolian rhodonite occur as an element of the hydrothermal replacement mineralization paragenesis in the Menderes-Izmir region of Turkey. The samples display some distinctive cathodoluminescence and thermoluminescence spectral luminescence emissions. The cathodoluminescence AC graphics of the rhodonite samples at 14 keV energy and frequencies of 90 and 180 Hz after excited by electron irradiation at room temperature indicate that there are three major spectral emissions, the dominant one being in the middle visible wavelength region (nearly yellow) at about 600 nm. Additionally, two lesser emission lines occur in the longer visible wavelength region (nearly red) at about 670 nm and in the shorter visible wavelength region (nearly blue) at about 490 nm. On the other hand, the cathodoluminescence data at 24 keV energy and frequencies of 9 and 90 Hz indicate that one distinctive spectral emission in the visible wavelength region between yellow and orange is present at about 620 nm. Minor emissions also exist in the shorter visible wavelength region (nearly lavender-blue) at about 420 nm and in the ultraviolet wavelength region at about 315 nm. Meanwhile, the cathodoluminescence DC spectra at energies of 14 and 24 keV the rhodonite samples are similar to the AC graphics regarding their wavelength positions and intensities, although their values are higher. These are at about 615, 600, 570, 500, 490, 430, 425, 395 and 305 nm, from the longer visible wavelength region to the ultraviolet wavelength region. It can be claimed that dominant cathodoluminescence emissions in the visible region are due to some extrinsic defects (chemical impurities) (dominant band at around 600 nm) and the others intrinsic defects (the nonbridging oxygen deficient centres with several precursors and self-trapped exciton) (minor bands at around 500, 400 and 300 nm) since the intensities and positions of these emissions are significantly different at two various energies, being due to increasing amounts of tetrahedral character with increasing electron density due to the presence of trace elements, taking into consideration the increased ionic character of the Si-O bond in the manganese silicate. The thermoluminescence glow curves of the rhodonite sample after X-ray beams for different irradiation times (10, 20 and 30 min) in temperatures ranging from 50-400 ºC display two main peaks which are observed at about 143 and 300 ºC. Even if raised to the maximum dose, the behaviour of the thermoluminescence curves remains nearly stable, but their intensities increase. Major cathodoluminescence emissions appearing at the yellow-orange region at around 600 nm suggest that the Anatolian rhodonite may have arisen from a host with relatively lower levels of the basic building elements (Mg, Na, K, P and Ba) and is consequently richer in free silica and calcium, i.e., of a more "neutral" character. However, some transition and rare earth elements (Fe, Mn, As, Bi, Cu, Ga, Pb, Tl, U and Zn) are significantly elevated. The presence of these major and minor cathodoluminescence and thermoluminescence emissions suggests that relatively higher levels of the transition elements can be attributed to a complicated geothermal system in the region.